1998
DOI: 10.1083/jcb.143.3.777
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Tau Protein Inhibits Kinesin-dependent Trafficking of Vesicles, Mitochondria, and Endoplasmic Reticulum: Implications for Alzheimer's Disease

Abstract: The neuronal microtubule-associated protein tau plays an important role in establishing cell polarity by stabilizing axonal microtubules that serve as tracks for motor-protein–driven transport processes. To investigate the role of tau in intracellular transport, we studied the effects of tau expression in stably transfected CHO cells and differentiated neuroblastoma N2a cells. Tau causes a change in cell shape, retards cell growth, and dramatically alters the distribution of various organelles, known to be tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
568
2
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 748 publications
(611 citation statements)
references
References 100 publications
35
568
2
6
Order By: Relevance
“…Nonetheless, numerous factors implicated in AD including oxidative stress (de la Monte et al, 2000;Perry and Smith, 1997;Smith et al, 1995), APO e (Tesseur et al, 2000), and APP-L (Torroja et al, 1999) have all been shown to affect axonal transport. The observation that AbPP can serve as a kinesin cargo receptor (Kamal et al, 2000(Kamal et al, , 2001 as well as the inhibition of kinesin-dependent transport by tau overexpression (Ebneth et al, 1998;Stamer et al, 2002) should not be overlooked. It would be interesting to see whether tau overexpression and Al affect intracellular transport via a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, numerous factors implicated in AD including oxidative stress (de la Monte et al, 2000;Perry and Smith, 1997;Smith et al, 1995), APO e (Tesseur et al, 2000), and APP-L (Torroja et al, 1999) have all been shown to affect axonal transport. The observation that AbPP can serve as a kinesin cargo receptor (Kamal et al, 2000(Kamal et al, , 2001 as well as the inhibition of kinesin-dependent transport by tau overexpression (Ebneth et al, 1998;Stamer et al, 2002) should not be overlooked. It would be interesting to see whether tau overexpression and Al affect intracellular transport via a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, a report demonstrating that increased GSK3b expression in a mouse model of tau overexpression decreased the axonopathy may seem to indicate that GSK3b may not play a role in the processes which lead to tau pathology and neuronal dysfunction in AD (Spittaels et al 2000). However, when tau is overexpressed in mice, axonopathy often occurs, which is likely due to the fact that tau inhibits kinesin-dependent processes leading to the inappropriate accumulation of proteins and organelles (Ebneth et al 1998;Stamer et al 2002). Therefore, in mice where tau levels are significantly increased due to the overexpression of exogenous tau, increased GSK3b activity may ameliorate the axonopathy by phosphorylating some of the excess tau, decreasing its microtubule binding and thus relieving the inhibitory effects on axonal transport.…”
Section: Discussionmentioning
confidence: 99%
“…30 Changes in tau protein, affecting stabilization of microtubules, are likely to impair axonal transport, 31,32 leading to changes in synaptic proteins and mitochondria axonal transport and ultimately culminating in "dying back" axons.…”
Section: ■ Tau Protein and Alzheimer's Diseasementioning
confidence: 99%